2004
DOI: 10.1111/j.1471-4159.2004.02308.x
|View full text |Cite
|
Sign up to set email alerts
|

Phospholipase D2 functions as a downstream signaling molecule of MAP kinase pathway in L1‐stimulated neurite outgrowth of cerebellar granule neurons

Abstract: Stimulation of the neuronal cell adhesion molecule L1 in cerebellar granule neurons (CGNs) enhances neurite outgrowth and this response is inhibited by the primary alcohol ethanol. Because primary alcohols suppress the formation of the signaling lipid phosphatidic acid (PA) by phospholipase D (PLD), this observation prompted us to investigate whether PLD plays a role in the L1-mediated neurite outgrowth in CGNs. In the cerebellum of postnatal day 8 mice, PLD2 protein was abundantly expressed, while PLD1 expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 55 publications
2
44
1
Order By: Relevance
“…The present study demonstrated that LPC-induced activation of PLD2 promoted neuritogenesis. Consistent with the stimulatory effect of PLD2 on neurite outgrowth, it has recently been reported that overexpression of PLD2 in PC12 cells elongated neurites induced by NGF stimulation (Watanabe et al, 2004b), and overexpression of PLD2 or treatment with exogenous PA, a second messenger produced by PLD activation, induced neurite outgrowth in cerebellar granule neurons (Watanabe et al, 2004a): PA induces reorganization of actin cytoskeleton and membrane trafficking Liscovitch et al, 2000;Exton, 2002), both of which are essential for neurite outgrowth. Actin cytoskeletal reorganization plays a key role in neurite outgrowth and guidance of primary cultured neurons (Daniels et al, 1998;Dickson, 2002), and PA directly interacts with several actin cytoskeleton-regulatory proteins, including PI4P-5-kinase, protein phosphatase 1 , and -COP.…”
Section: Discussionmentioning
confidence: 69%
“…The present study demonstrated that LPC-induced activation of PLD2 promoted neuritogenesis. Consistent with the stimulatory effect of PLD2 on neurite outgrowth, it has recently been reported that overexpression of PLD2 in PC12 cells elongated neurites induced by NGF stimulation (Watanabe et al, 2004b), and overexpression of PLD2 or treatment with exogenous PA, a second messenger produced by PLD activation, induced neurite outgrowth in cerebellar granule neurons (Watanabe et al, 2004a): PA induces reorganization of actin cytoskeleton and membrane trafficking Liscovitch et al, 2000;Exton, 2002), both of which are essential for neurite outgrowth. Actin cytoskeletal reorganization plays a key role in neurite outgrowth and guidance of primary cultured neurons (Daniels et al, 1998;Dickson, 2002), and PA directly interacts with several actin cytoskeleton-regulatory proteins, including PI4P-5-kinase, protein phosphatase 1 , and -COP.…”
Section: Discussionmentioning
confidence: 69%
“…However, in primary mouse cerebellar granule neurons, PLD2 exhibited a primarily intracellular punctate (vesicular) distribution (69). Subcellular fractionation of rat liver demonstrated predominant localization of endogenous PLD2 in the Golgi apparatus and light membranes (70).…”
Section: Discussionmentioning
confidence: 99%
“…Collectively, our findings indicate that PLD1 increases surface delivery of ␤APP at axonal terminals and rescues impaired axonal growth and neurite branching in FAD PS1 mutant neurons. It is also possible that growth-promoting effects of PLD1 may be partially mediated through its modulation of Rho pathways by activation of PLD2, which has also been implicated in neurite outgrowth (24,25), or through activation of phosphatidylinositol-4-phosphate 5-kinase (PIP5K) to generate phosphatidylinositol 4,5-bisphosphate [PI(4,5)P 2 ], a cofactor for both PLD1 and PLD2 (26).…”
Section: Discussionmentioning
confidence: 99%